2023
DOI: 10.3390/math11183844
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Hybrid Multi-Objective Optimization Method Coupling Global Evolutionary and Local Gradient Searches for Solving Aerodynamic Optimization Problems

Fan Cao,
Zhili Tang,
Caicheng Zhu
et al.

Abstract: Aerodynamic shape optimization is frequently complicated and challenging due to the involvement of multiple objectives, large-scale decision variables, and expensive cost function evaluation. This paper presents a bilayer parallel hybrid algorithm framework coupling multi-objective local search and global evolution mechanism to improve the optimization efficiency and convergence accuracy in high-dimensional design space. Specifically, an efficient multi-objective hybrid algorithm (MOHA) and a gradient-based su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Buffinton et al [18] used the Kirton Adaption-Innovation Inventory (KAI) to determine cognitive styles. They concluded that cognitive style theory may be applied to characterize and better understand the personal While engineering design has been explored from various different perspectives, including optimization [2][3][4], reliability [5][6][7][8], manufacturability [9] and decision making [10], among others, there are limited studies of the human dynamics that are inherent to engineering organizations. To gain a better understanding of engineering project management, we clearly need to model the processes and people involved in executing them.…”
Section: Background and Literature Surveymentioning
confidence: 99%
“…Buffinton et al [18] used the Kirton Adaption-Innovation Inventory (KAI) to determine cognitive styles. They concluded that cognitive style theory may be applied to characterize and better understand the personal While engineering design has been explored from various different perspectives, including optimization [2][3][4], reliability [5][6][7][8], manufacturability [9] and decision making [10], among others, there are limited studies of the human dynamics that are inherent to engineering organizations. To gain a better understanding of engineering project management, we clearly need to model the processes and people involved in executing them.…”
Section: Background and Literature Surveymentioning
confidence: 99%
“…Moreover, owing to their flexible architecture and versatile capability, MOEAs have also been applied into many real-world complex optimization problems [28][29][30][31][32] including discrete optimization problems such as network community detection problems [33], neural network search problems [34], task offload problems [35,36], and feature selection problems [37][38][39]. In particular, feature selection has been widely used as a data preprocessing and dimensionality reduction technique for tackling large-scale classification datasets by selecting only a subset of useful features [40].…”
Section: Introductionmentioning
confidence: 99%
“…There are also many other kinds of excellent MOEAs [27][28][29], including the novel multi-objective particle swarm optimization algorithm proposed by Leung et al [30], which adopted a hybrid global leader selection strategy with two leaders: one for exploration and the other for exploitation. Moreover, MOEAs have also been used to solve many real-world optimization problems [31][32][33], such as system control [34,35], community detection [36,37], network construction [38][39][40], task allocation [41,42], and feature selection [43,44]. Generally speaking, feature selection is normally used to select useful feature subsets for classification [45], while the bi-objective feature selection problem usually seeks to minimize both the classification error and the number of selected features [46].…”
Section: Introductionmentioning
confidence: 99%